Effects Of Demonstrative And Discovery Teaching Strategies On Senior Secondary School Two (S.S.2) Students’ Achievement In Oral English In Bayelsa State. - Bokolo, Faith; Uwah, Idongesit Victor; Simeon, Norman (Advances in Social Sciences Research Journal, 2020)
The researchers investigated the effects of Demonstrative and Guided Discovery teaching strategies on Senior Secondary School Two (2) students’ achievement in Oral English in Bayelsa State. A quasi-experimental design approach was adopted, using a sample of Sixty (60) students comprising of both male and female from Yenagoa Local Government Area of Bayelsa State. Data collated were analyzed using mean standard deviation and the Analysis of Covariance (ANCOVA). This research was guided by Four (4) research questions and hypothesis. The instrument used for data collection was the Oral English achievement test (OEAT), The instrument contained 25 multiple choice items marked over 100 which were standardized. KR20 was used to determine a reliability coefficient of 0.95. The test was based on human sound system. The result analyzed showed among others that there was a significant difference (P=0.000<0.05) between demonstrative and discovery, and demonstrative and conventional methods of teaching. On the other hand, no significant difference existed (p=0.314>0.05) between discovery and conventional method of teaching. The significance difference observed between the various teaching methods is indicative that the demonstrative method is the most effective in the teaching of Oral English. Some recommendations were made on enhancing Oral English language skill acquisition such as provision of e-learning facilities in schools, continuous education for Oral English teachers among others.